Global control in Pseudomonas fluorescens mediating antibiotic synthesis and suppression of black root rot of tobacco. - Laville, J (1992)
Pseudomonas fluorescens CHA0 colonizes plant roots, produces several secondary metabolites in stationary growth phase, and suppresses a number of plant diseases, including Thielaviopsis basicola-induced black root rot of tobacco. We discovered that mutations in a P. fluorescens gene named gacA (for global antibiotic and cyanide control) pleiotropically block the production of the secondary metabolites 2,4-diacetylphloroglucinol (Phl), HCN, and pyoluteorin. The gacA mutants of strain CHA0 have a drastically reduced ability to suppress black root rot under gnotobiotic conditions, supporting the previous observations that the antibiotic Phl and HCN individually contribute to the suppression of black root rot. The gacA gene is directly followed by a uvrC gene. Double gacA-uvrC mutations render P. fluorescens sensitive to UV irradiation. The gacA-uvrC cluster is homologous to the orf-2 (= uvrY)-uvrC operon of Escherichia coli. The gacA gene specifies a trans-active 24-kDa protein. Sequence data indicate that the GacA protein is a response regulator in the FixJ/DegU family of two-component regulatory systems. Expression of the gacA gene itself was increased in stationary phase. We propose that GacA, perhaps activated by conditions of restricted growth, functions as a global regulator of secondary metabolism in P. fluorescens.